Decreased Soluble Receptor of Advanced Glycation End Product Levels Correlated with Inflammation in Silicosis - Heliang Liu; Jingjing Ma; Tian Jiang; Enhong Li; Xiaokun Zhao; Ying Wang; Jie Cui; Xiaohui Hao; Lingli Guo (Mediators of Inflammation)
Silicosis is a devastating disease caused by inhalation of silica dust that leads to inflammatory cascade and then scarring of the lung tissue. Increasing evidences indicate that soluble receptor for advanced glycation end products (sRAGE) is involved in inflammatory diseases. However, no data on the possible relationship between sRAGE and inflammation of silicosis are available. In this study, serum from subjects with silicosis (n=59) or from healthy controls (HC, n=14) was analyzed for the secretion of sRAGE, tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), transforming growth factor-β1 (TGF-β1), and oxidized low-density lipoprotein (ox-LDL). The associations between sRAGE and cytokines and ox-LDL and lung function were assessed by Pearson’s correlation analyses. Mean levels of serum sRAGE were lower in silicosis than those in controls (p<0.05). The subjects who had a longer term of occupational exposure had higher levels of sRAGE (p<0.05). The secretion of TNF-α, IL-1β, IL-6, TGF-β1, and ox-LDL was significantly higher in the silicosis group than that in the HC group (p<0.05). Furthermore, the levels of sRAGE were negatively correlated with TNF-α, IL-6, IL-1β, and ox-LDL. There is no correlation between sRAGE and TGF-β1 and lung function. The optimal point of sRAGE for differentiating silicosis from healthy controls was 14250.02 pg/ml by ROC curve analysis. A decrease in serum sRAGE and its association with inflammatory response might suggest a role for sRAGE in the pathogenesis of silicosis.